Exploring Antecedents Of Attitude Towards Controversial Advertising - Ernest Cyril, de Run; Hiram, Ting (2013)
This study aims to explore the antecedents to attitude about advertising of two controversial products, namely political parties and sexual diseases prevention. The theory of reasoned action was used to provide theoretical basis to exploring beliefs about adverting and explaining attitude. Accordingly, qualitative approach by means of personal interview was adopted, and all interview transcripts were later content-analyzed by multiple coders. The findings show that there are 11 statements of belief about the advertising of political parties and 6 statements about sexual diseases prevention. Even though the advertising of both products are mainly considered as a source of information, their descriptions are very different. While advertising of political parties is chiefly believed to be misleading and for personal gain, advertising of sexual diseases prevention is regarded as a form of education. Thus the former must be carried out with care to prevent potential negative responses, and the latter should be done without exaggeration to achieve its intent. This reinforces the understanding of attitude towards controversial advertising by its type, and beliefs about advertising which might be different and thus create controversy.